IMPLEMENTASI METODE MUROTTAL SEBAGAI MEDIA PASSIVE LISTENING UNTUK MEMPERCEPAT HAFALAN SURAT PENDEK SISWA TK PUTRA NURUL IMAN 3 - Nurul Fajar Mirosi; Eka Danik Prahastiwi (LPPM STAI La Tansa Mashiro, 2026)
This study examines the implementation of murottal method as a passive listening medium to accelerate the memorization of short Qur'anic chapters among kindergarten students at TK Putra Nurul Iman 3. Early childhood is a phase of rapid cognitive and linguistic development, making repeated, structured, and meaningful auditory exposure such as Qur'anic murottal recitation highly effective in supporting memory consolidation and habit formation. Using a descriptive qualitative approach with observation, in-depth interviews, and documentation, this study reveals that regular murottal as ambient sound during daily activities significantly increases children's exposure to Qur'anic verses. Findings show that students demonstrate improved echoic memory, greater motivation, and enhanced concentration during memorization sessions. The study recommends systematic integration of murottal passive listening into early childhood Islamic education curricula as an effective, enjoyable, and developmentally appropriate strategy